Disaster Intelligent Perception and Emergency Command of Power Grid - Yu, Zhen.; Feng, Jie.; Tang, Shiyang; Liu, Zeyu.; Yan, Yiran; Luo, Na.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This open access book addresses the current technical problems of low efficiency of emergency site information collection, lack of flexibility of emergency information interaction, lack of fusion analysis technology and disaster loss prediction model, and low intelligence of emergency auxiliary decision making. The content contains research on multiple information collection technology of power grid disaster loss, fusion analysis and prediction technology of power grid disaster loss information, and real-time information interaction technology between emergency site and command center in this work. This book illustrates the process of developing a prototype system for grid disaster perception and emergency command, which realizes the functions of grid disaster perception and emergency auxiliary decision-making and visualization command. The prototype intelligent perception and emergency command system for power grid disasters has been piloted in several units. It provided support fordisaster loss prediction, disaster damage perception, and emergency command auxiliary decision-making in the earthquake in Sichuan, China, as well as the heavy rainfall in Zhejiang, China and Typhoon No. 9 "Lupi" that registered in Fujian, China, which significantly improved the emergency disposal Work efficiency.
Introduction -- Network awareness and emergency command fundamentals -- Multiple information collection technology of power network disaster loss -- Grid disaster information fusion and integrated prediction technology -- Real-time interaction technologies for grid emergency information -- Grid emergency decision technology -- Intelligent sensing and emergency command system for power grid disaster .
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Electric power distribution; Electric power production; Energy Grids and Networks; Mechanical Power Engineering